Transcriptome profile of bovine elongated conceptus obtained from SCNT and IVP pregnancies. Issue 4 (26th March 2013) - Betsha, Simret; Hoelker, Michael; Salilew‐Wondim, Dessie; Held, Eva; Rings, Franka; Große‐Brinkhause, Christine; Cinar, Mehmet Ulas; Havlicek, Vitea; Besenfelder, Urban; Tholen, Ernst; Looft, Christian; Schellander, Karl; et al.
Abstract In the present study we analyzed the gene expression changes induced by somatic cell nuclear transfer (SCNT) and in vitro production (IVP) in bovine elongated embryos using Affymetrix bovine genome array. For this, Day‐16 bovine embryos from SCNT, IVP, and artificial insemination (AI) were recovered from recipients and used for transcriptome analysis. Despite comparable in vivo development rates, considerable reduction in elongation size was observed in SCNT compared to non‐cloned embryos (93.3 mm for SCNT vs. 186.6 mm and 196.3 mm for IVP and AI embryos, respectively). Gene expression analysis revealed that the transcript levels of 477 genes, which are involved in various pathways including arginine and proline or glycerolipid and fatty acid metabolism, were significantly altered in SCNT compared to AI embryos. Similarly, 365 genes were differentially expressed in IVP embryos compared to AI. Thus, several pathways including TNRF‐1 signaling and tight junction pathways were affected. To predict whether the altered transcripts were associated with culture condition or errors in transcriptional reprogramming, unique or common differentially expressed genes were analyzed in SCNT and IVP embryos compared to AI or fibroblast donor cells. Accordingly, 71 transcripts were found to be not transcriptionally reprogrammed, as their expression resembled the donor cells more than AI embryos; the remaining transcripts were either partially or incompletely reprogrammed. In conclusion, the present study identified deviations in elongation size, gene expression, and the corresponding molecular pathways in Day‐16 SCNT and IVP conceptuses compared to their AI counterparts, which may subsequently be associated with the outcome of fetal development. Mol. Reprod. Dev. 80: 315–333, 2013. © 2013 Wiley Periodicals, Inc.